Penerapan Metode Outdoor Learning pada Mata Pelajaran PAI di SD Alam Mutiara Umat - Choirunnisa’ Erlinasari; Yoga Sari Prabowo (Journal on Education, 2024)
The purpose of this study is to evaluate the implementation of learning methods outside the classroom in Islamic Religious Education subjects applied at SD Alam Mutiara Umat Panggungrejo, Tulungagung Regency. Learning outside the classroom is applied 2 times a week based on the material taught, in addition to learning on subjects, Islamic Religious Education is also associated with various school activities and activities, namely, morning motivation, Usmani, fiqh nisa, and pre-missionary training activities. The method applied is descriptive qualitative with data collection through observation, interviews, and documentation. Informants in this study included school principals, Islamic Religious Education teachers, and homeroom teachers. The application of outdoor learning methods in Islamic Religious Education at SD Alam Mutiara Umat can be changed to be more effective to improve the quality of learning and facilitate the improvement of the student learning experience.